Communicating the keywords of sendai framework: A corpus-based approach - Thiruchelvam S.; Jin N.Y.; Tong C.S.; Husin N.B.M.; Ghazali A.; Kamal A. (Primrose Hall Publishing Group, 2023)
The Sendai Framework provides insights in terms of multiple levels of governance and recommendations on reduction of disaster risks. It is crucial that the essence of the framework is fully comprehended especially in communicating the priorities to various parties and stakeholders. The interpretation of the framework by various professional organisations, academia and stakeholders, for the purpose of planning and implementation, can be a challenging and laborious task. This paper will present an alternative perspective that simplifies the interpretation of knowledge dissemination (content analysis), especially when connecting the Sendai Framework key essence using a corpus-based approach. 'Keywords' will be used as a lens for community and stakeholders involved in disaster risk reduction planning or execution. This is achieved by a corpus-based investigation of the Sendai Framework Blueprint (official document). A keyword analysis was performed to identify words associated with the Sendai Framework core and of the potential pedagogic values therein. This paper suggests appropriate and continuous interpretation of the analysed content, in order to achieve improved disaster risk reduction communication within the community of stakeholders. 2019 International Press of Boston, Inc.